Antibiotic therapy in hospitalized patients with COVID-19: A Systematic review and Meta-analyses - Coaguila Cusicanqui, Luis A. (2022)
Introduction: The aim of the study is based on determine whether the use of empirical antibiotic therapy increases the risk of death in adult patients older than 18 years hospitalized with COVID-19. Material and Methods: A systematic review and meta-analysis were performed, taking into account retrospective and prospective studies. The electronic databases Medline/PubMed, Embase, LILACS, and CINAHL were used for the systematic search in the period from December 2019 to May 2021. Odds Ratio and 95% confidence intervals were calculated using the random effect, depending on whether or not heterogeneity exists, the Funnel Plot graph was elaborated to assess the risk of bias. Results: 528 articles were located, which met the inclusion and exclusion criteria, and the eligibility of the full texts of 90 studies was evaluated, resulting in 10 articles. The Odds Ratio of the 10 studies is 1.55 (1.20-2.01), in favor of the non-use of antibiotics, with an I2 of heterogeneity between studies of 50%, and the empirical antibiotic therapy guided with procalcitonin < 0.5 ng/dl the Odds Ratio was 28.99 (10.17-82.64) with an I2 of heterogeneity of 0%. Conclusion: The results indicate that administering antibiotics without evidence of microbiological data increases mortality in these patients and, on the contrary, not using empirical antibiotic therapy reduces mortality in patients infected with severe COVID-19 who arrived at the hospital.